SISTEM INFORMASI PENDAPATAN JASA BERBASIS DESKTOP SEBAGAI UPAYA PENGENDALIAN KAS PADA PERUSAHAAN JASA - Indria Widyastuti; Dewi Yuliandari; Gelistia Rahmah (Jurnal Akrab Juara, 2019)
Each company is required to implement an accounting system that is in accordance with the conditions of each company. One of the systems used by the company is a system of income accounting and cash receipts. Cash problem is something that requires special handling, especially for large, medium and small companies. In the cash income and expenditure system, it is necessary to have a good procedure that will be in accordance with established management policies. By using computerized information systems, computerized data storage systems cause all stored data to be more secure, and computerized systems can speed up the process of recording income and archiving available data. Desktop-based applications are applications that are widely used, because of easier use and in a more attractive form and appearance. The use of applications makes it easy to process data to be more automatic and the data that is processed will become structured information.